“Violence is the woman you never had” : Trauma of Women in Christina Reid's The Belle of the Belfast City (Journal of the College of Education for Women, 2025)
This paper examines The Belle of the Belfast City by Christina Reid through the lens of trauma theory as outlined by Judith Herman and Cathy Caruth. The play depicts the influence of the Troubles in Northern Ireland as a religious and sectarian conflict between Protestants and Catholics on women. Reid's work is mainly about the reunion of three generations of working-class Protestant women during the time of the Anglo-Irish agreement in 1985.The play's female characters face many obstacles, including racism, forced migration, religious persecution, economic struggle, social exclusion, and abuse. The study presents how religion is used as a tool to justify violence against women. Women become targets of verbal and physical abuse, violence, and discrimination based on religious identification. This study delves into the ways trauma impacts the lives and identities of the characters, shedding light on the crucial role of memory in their recovery. Moreover, the study examines use of symbols and songs to make the women's trauma experiences stronger. It shows both the visual and emotional parts of their lives and stresses the healing power of art and cultural expression.